2022
DOI: 10.1111/ppa.13574
|View full text |Cite
|
Sign up to set email alerts
|

Phenology‐regulated defence mechanisms as drivers for Fusarium basal rot in onion (Allium cepa)

Abstract: Fusarium basal rot (FBR) is one of the most destructive soilborne diseases in onion (Allium cepa) worldwide, and can occur throughout the entire crop cycle. The disease can cause pre-and postemergence seedling death and pre-and postharvest bulb rot, resulting in overall yield losses of between 30% and 50% (Dauda et al., 2018;Ozer et al., 2004). While Fusarium oxysporum f. sp. cepae is widely recognized as the main causal agent of FBR, F. proliferatum is considered an emerging pathogen associated with this dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 32 publications
3
13
0
Order By: Relevance
“…These results match with those of other authors who have reported that there are Fusarium species responsible for seedling damping-off (O'Donnell et al, 2015;Kee et al, 2020;Dongzhen et al, 2020). Le et al (2022) reported that fumonisin B1 generate by Fusarium species appeared to be a virulence factor specific for the seedling stage.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results match with those of other authors who have reported that there are Fusarium species responsible for seedling damping-off (O'Donnell et al, 2015;Kee et al, 2020;Dongzhen et al, 2020). Le et al (2022) reported that fumonisin B1 generate by Fusarium species appeared to be a virulence factor specific for the seedling stage.…”
Section: Discussionsupporting
confidence: 92%
“…Inoculations with F. oxysporum and F. acutatum caused severe seedling damping-off at 21 DAS and 45 DAS, but there was no difference between F. falciforme treatment and the control. Defense-related genes in seedlings were differently expressed depending on the aggressiveness of Fusarium isolates and the outcome of Fusarium basal rot is driven by the phenology of onion (Le et al, 2022). These results match with those of other authors who have reported that there are Fusarium species responsible for seedling damping-off (O'Donnell et al, 2015;Kee et al, 2020;Dongzhen et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…proliferatum isolates significantly decreased seedling emergence. In addition, Le et al (2022) recently showed that both F . oxysporum and F .…”
Section: Discussionmentioning
confidence: 99%
“…Our results agree with the previous study by Kintega et al (2020), who showed that inoculation of onion seeds with both F. oxysporum and F. proliferatum isolates significantly decreased seedling emergence. In addition, Le et al (2022) recently showed that both F. oxysporum and F. proliferatum isolates significantly reduced seedling root length and caused damping-off symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation